In-field dependences of the critical current density Jc in GdBa2Cu3O7-d coated conductors produced by Zr irradiation and post-annealing at low temperatures - Haberkorn, N. (2019)
Fil: Haberkorn, N. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Universidad Nacional de Cuyo; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina